Influence of Food and Beverage Companies on Retailer Marketing Strategies and Consumer Behavior - Hecht, Amelie A. (Int J Environ Res Public Health, 2020)
The retail food environment plays an important role in shaping dietary habits that contribute to obesity and other chronic diseases. Food and beverage manufacturers use trade promotion—incentives paid to retailers—to influence how products are placed, priced, and promoted in stores. This review aims to: (1) catalogue trade promotion practices that manufacturers use to influence retailer marketing strategies, and (2) describe how these retailer marketing strategies affect consumer purchasing behavior and attitudes. Researchers searched five databases, Academic Search Ultimate, Business Source Ultimate, PsycINFO, PubMed, and Web of Science, to identify literature from industry and academic sources published in English through November 2019. Twenty articles describing manufacturer trade promotion practices were synthesized and provided insight into four types of trade promotion practices: category management, slotting allowances, price discounts, and cooperative advertising. Fifty-four articles describing the impact of retailer marketing on consumers were synthesized and graded for quality of evidence. While comparison across studies is challenging, findings suggest that retailer marketing strategies, such as price promotions and prominent placement, lead to increased sales. Results can guide efforts by policymakers, public health practitioners, and food retailers to design retail environments that improve healthy eating while maintaining retailer financial interests. Additional research should measure the impact of retailer marketing strategies on consumer diet quality and retailer outcomes (e.g., return-on-investment).